Impact of Sunflower Frontline Demonstrations in Akola District of Maharashtra - R. Venkattakumar , M.Padmaiah , C. Sarada , A.M.Mahajan , M.K.Moon, S.N.Deshmukh, (Indian Journal of Extension Education, 2022)
To assess the determinants of technology adoption by sunflower farmers towards improved sunflower(Helianthus annuus L.) production technologies, a study was conducted inAkola district ofMaharashtra during September 2009. The assessment was done on a comparative basis between 60 farmers who participated in the Front Line Demonstrations (FLDs) organized by Crop Research Unit of Dr. Panjabrao Deshmukh Krishi Vidyapeeth (PDKV), Akola, Maharashtra (FLD farmers) and farmers who did not participate in the FLD programme but belong to the same villages wherein FLDs were organized (non-FLD farmers). The respondents were selected through multi-stage random sampling procedure. There was highly significant difference between FLD and non-FLD respondents with respect to their adoption behaviour and sunflower productivity. Therewas significant difference among non-FLD farmers with small,mediumand large size of land holdings with respect to their adoption behaviour and sunflower productivity, while there was no such difference among the FLDfarmers.Most of the non-FLD farmers had low tomediumlevel of sunflower productivity, whilemost of the FLD farmers had medium to high level of sunflower productivity. Overall, there was 11% mean seed yield increase obtained by the FLD farmers over that of non-FLD farmers with Rs.2254/ha additional net returns. The personal, socioeconomical, biotic and abiotic determinants of sunflower production and perceived information needs were assessed and the strategies were suggested for improving the sunflower production scenario in the study area.